Economic feasibility of on-farm processing and value chain of cashewnut in West Garo Hills of Meghalaya - Hatai, Lakshmi Dhar (Journal of Plantation Crops, 2018)
Value chain of cashew has got greater potential in income generation and farm level employment. It was observed that increase in farm size is accompanied by higher productivity and remunerative price fetched by large farmers as compared to other categories of cashew growers. The net price received by the farmers was the highest when they sold their produce directly to consumers. The highest benefit cost ratio was achieved by the large farms because of judicious expenditure in cashew production and obtaining a sizeable amount of returns. In the West Garo Hills, cashew value chain needs application of modern technology and proper management practices for better production and marketing. The study highlight that the prospect of cashew value chain in Meghalaya is bright as the trend of other traditional crop production in the potential areas is quite encouraging for the organic cashew farming. There is enough scope for enhancing organic produce of cashew. Direct marketing of cashew produce always fetch good price for the producer but it is not possible for all categories of farmers. Therefore, formation of cooperative societies of cashew growers is suggested for marketing of various inputs as well as outputs of cashew produce.